BRCA1/2 germline missense mutations: a systematic review. Issue 3 (May 2018) - Corso, Giovanni; Feroce, Irene; Intra, Mattia; Toesca, Antonio; Magnoni, Francesca; Sargenti, Manuela; Naninato, Paola; Caldarella, Pietro; Pagani, Gianmatteo; Vento, Annarita; Veronesi, Paolo; Bonanni, Bernardo; et al.
Abstract : Hereditary breast and ovarian cancer is an inherited syndrome associated with BRCA1/2 germline defects. The identified mutations are classified as missense, large deletion, insertion, nonsense and splice-site variants with a deleterious impact on BRCA1/2 function. Part of these forms the well-documented truncating mutations, and missense variants represent a clinical dilemma as the pathogenic role is yet to be clearly shown. In this systematic review, we collected these missense variations with a documented deleterious function. We focused on English language articles from MEDLINE. This study included all BRCA1/2 germline missense mutations identified in breast and ovarian cancer patients. The method of this study followed the 'PRISMA statement for reporting systematic reviews and meta-analyses'. A total of 61 BRCA1/2 germline and pathogenic missense mutations were identified: 70.5% affected BRCA1 and 29.5% BRCA2, respectively. In BRCA1, the majority of mutations were located in the BRCA C-terminus (48.8%), leading to a disruption of function. Conversely, no specific associations were verified between mutations and the BRCA2 gene. The European population was the most affected by BRCA1 and the Asian population by BRCA2 mutant patterns. The identification of novel BRCA1/2 missense mutations requires specific genetic tests to assess pathogenicity. With this systematic review, we are, to the best of our knowledge, the first to collect the overall amount of data on these pathogenic mutants with the aim of improving the management of carriers and their kindred.